High-frequency transcranial magnetic stimulation improves motor performance in individuals with incomplete spinal cord injury - de Araújo, Amanda Vitória Lacerda; Barbosa, Valéria Ribeiro Nogueira; Galdino, Gilma Serra; Fregni, Felipe; Massetti, Thais; Fontes, Sara Lynn; de Oliveira Silva, Danilo [UNESP]; da Silva, Talita Dias; de Mello Monteiro, Carlos Bandeira; Tonks, James; Magalhães, Fernando Henrique (Springer Nature, 2019)
The aim of the present study was to investigate the effects of high-frequency rTMS on motor function in individuals with iSCI, so as to explore the clinical utility of rTMS in this population. This prospective trial enrolled 15 individuals who were at least six months post incomplete SCI (aged 18–60 years), recruited through referral by medical practitioners or therapists. The study design involved both rTMS-sham and rTMS-active protocols. The protocol included five sessions (one session daily) of high-frequency rTMS (5 Hz) over the bilateral lower limb motor area positioned at the primary motor cortex (M1). In the sham condition, the coil was disconnected from the rTMS device so as to ensure the interruption of the magnetic field. American Spinal Injury Association Impairment Scale (ASIA) motor scores were assessed at baseline (before intervention), after rTMS-sham and after rTMS-active, and the changes from baseline motor values provided by the ASIA score were used to assess the effects of both rTMS-sham and rTMS-active on the motor performance of individuals with iSCI. rTMS active was associated with significantly larger changes in ASIA motor scores as compared to rTMS-sham (T(1, 14) = 5,359, P < 0.001, ES = 0.67). We conclude that rTMS has produced positive results in improving participants’ motor function, thereby indicating that rTMS might be used as an effective clinical tool in the rehabilitation of individuals with SCI.
Keywords: Motor rehabilitation; Non-invasive brain stimulation; Plasticity